2018
DOI: 10.1101/483958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CDK12 loss in cancer cells affects DNA damage response genes through premature cleavage and polyadenylation

Abstract: damage response (DDR) and mRNA processing genes. Yet, the mechanism(s) by which it achieves this selectivity remains unclear. Using a highly selective CDK12/13 inhibitor, THZ531, and nascent RNA sequencing, we show that CDK12 inhibition results in gene length-dependent elongation defects, leading to premature cleavage and polyadenylation (PCPA) as well as loss of expression of long (>45 kb) genes, a substantial proportion of which participate in the DDR. This early termination phenotype correlated with an incr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…It remains to be determined whether this CDK12‐mediated effect on ALE splicing in breast cancer is dependent on RNAP II CTD or another undescribed pathway of CDK12. Recent studies showed that CDK12 not only play a role in ALE regulation but also in protecting the cells from premature CpA and allowing expression of long genes, a sizable portion of which include DDR genes (Krajewska et al, ). p38 kinase (Danckwardt et al, ) and protein kinase C (PKC)δ (W. Li et al, ) are involved in the modulation of poly(A) signal usage of prothrombin pre‐mRNA in response to the stress‐inducing agent anisomycin and BIK pre‐mRNA in response to DNA damage, respectively.…”
Section: Alternative Polyadenylationmentioning
confidence: 99%
“…It remains to be determined whether this CDK12‐mediated effect on ALE splicing in breast cancer is dependent on RNAP II CTD or another undescribed pathway of CDK12. Recent studies showed that CDK12 not only play a role in ALE regulation but also in protecting the cells from premature CpA and allowing expression of long genes, a sizable portion of which include DDR genes (Krajewska et al, ). p38 kinase (Danckwardt et al, ) and protein kinase C (PKC)δ (W. Li et al, ) are involved in the modulation of poly(A) signal usage of prothrombin pre‐mRNA in response to the stress‐inducing agent anisomycin and BIK pre‐mRNA in response to DNA damage, respectively.…”
Section: Alternative Polyadenylationmentioning
confidence: 99%
“…2A). 34,35,63,68 However, while the binding of p27 to A and D-cyclins is conserved, significant differences are found when comparing inhibitor binding to the kinase subunit in the CDK2-cyclin A-p27 and CDK4-cyclin D1-p27 structures (Fig. 2B).…”
Section: Recent Progress In Cdk Structure-function Studiesmentioning
confidence: 99%
“…38,67 p21 and p27 are classed as intrinsically disordered proteins and fold upon binding to CDK-cyclin complexes. 37,64,65 To act as an inhibitor, exposure of the p27 D1 region (residues [27][28][29][30][31][32][33][34][35][36][37] which contains an RXL motif that binds to the cyclin recruitment site (Fig. 2A) primes binding of the p27 kinase inhibitory domain (KID, residues 28-89) via conformational sampling.…”
Section: Recent Progress In Cdk Structure-function Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 CDK12 plays a vital biological role in transcription, mRNA splicing, the cell cycle and DNA damage response (DDR) repair. [5][6][7][8] CDK12 overexpression increases DNAJB6-L through ALE splicing which increases the aggressiveness of breast cancer cells. 5 High CDK12 expression promotes IRS1-p85-ErbB receptor binding and activates the ErbB-PI3K-AKT signaling cascade for HER2-positive breast cancer development.…”
Section: Introductionmentioning
confidence: 99%